Mexico : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance report on Mexico discusses public investment management assessment (PIMA). It evaluates 15 key institutions in terms of their institutional strength and effectiveness across the planning, allocation, and implementation phases of the PIM cycle, identifies strengths and weaknesses in the existing PIM framework, and produces an action plan to improve PIM. This assessment found that most of Mexico's institutions scored as medium strength in terms of institutional design and effectiveness. It is recommended to include a medium-term target for the public sector borrowing requirement, introduce an independent body to review and assess the quality of the macro-fiscal projections, and amend the fiscal rule's escape clause so it is only used in exceptional circumstances. In addition, expand the economic assumptions report to include more information on fiscal strategy and analyses of medium-term fiscal parameters. It is also recommended to develop mechanisms for coordination of public investment plans at federal and subnational levels to enhance efficiency and synergies of planning and investment prioritization.